Respons Antibodi terhadap Penyakit Tetelo pada Ayam yang Divaksin Tetelo dan Tetelo-Flu Burung (NEWCASTLE DISEASE/ND ANTIBODY RESPONSE OF CHICKENS VACCINATED WITH ND SINGLE AND COMBINED ND AND AVIAN INFLUENZA VACCINES) - Kencana, Gusti Ayu Yuniati; Suartha, Nyoman; Simbolon, Mesakh Parlindungan; Handayani, Arini Nur; Ong, Steffi; ., Syamsidar; Kusumastuti, Aprillia (Jurnal Veteriner, 2015)
The aim of this study was to investigate antibody response of specific pathogen-free (SPF) chickens vaccinatedwith single inactivated Newcastle disease (ND) vaccine and combined inactive ND and avian influenza(AI) vaccines and to known the efficacy of both vaccines. The vaccines used were killed ND vaccine andkilled ND-AI vaccine produced by PT. Sanbio Laboratories Bogor, West Java. SPF chickens were vaccinatedwith 3 different doses. Antibody titer of SPF chickens against ND virus were determined byhaemagglutination inhibition (HI) test. As many as 130 two week old SPF chickens were used and theywere divided into 2 groups (A and B) consisting of 60 chickens and 10 chickens were used as control withoutvaccine. Group A chickens were vaccinated with ND-K vaccine and group B were vaccinated with combinedkilled ND-AI vaccines. Each group was further divided into 3 subsgroups (1, 2 and 3) consisting 20 chickens.Subgroups 1, 2 and 3 were vaccinated intramuscularly respectively with intramuskular 1, 1/10 and 1/100doses of each vaccines. Antibody response of chickens against ND virus was examined before vaccinationand every three week after vaccination and was expresses as geometric mean titre (GMT) HI units. Theresult showed that the titre antibody against ND increased at the second week following the vaccination.The antibody titer against ND virus of chickens vaccinated single killed ND at the second week in eachdose were 6.05 GMT HI unit, 4.05 GMT HI unit, and 0.9 GMT HI unit. The antibody titre at the third week were 7.90 GMT HI unit ,5.40 GMT HI unit and 2.20 GMT HI unit. The antibody titre against ND virus ofchickens vaccinated with combined ND-AI vaccine at the second week were 6.30 GMT HI unit , 4.15 GMTHI unit , and 2.05 GMT HI unit. At the third week, the antibody titre against ND virus of chickensvaccinated with combined ND-AI vaccine in each subgroup were 7.45 GMT HI unit, 5.60 GMT HI unit , and2.40 GMT HI unit . It showed that the antibody titers at single doses of killed ND vaccine (7.90 GMT HIunit) and combined ND-AI vaccine (7.45 GMT HI unit) at the third week after vaccination were both stilleffective as both titres were above standard protective titre.
Keywords: antibody titre, ND-K vaccine, ND-AI vaccine, SPF chicken